Nonlocal Problem for a Fourth-Order Equation - Abulov M. O; Nazarova R. A (Genius Journals, 2025)
This article considers a nonlocal problem for a fourth-order equation in a quadrilateral domain. Using the Galerkin method, the existence and uniqueness of a generalized soliton in a Sobolev space is proven under certain conditions on the coefficients and the righthand side of the equation
Keywords: nonlocal problem; quadrangular domain; generalized solution